Chromosome-Scale Genome Assembly for Chinese Sour Jujube and Insights Into Its Genome Evolution and Domestication Signature - Shen, Lian-Ying; Luo, Hang; Wang, Xiao-Ling; Wang, Xue-Meng; Qiu, Xiao-Jing; Liu, Hui; Zhou, Shan-Shan; Jia, Kai-Hua; Nie, Shuai; Bao, Yu-Tao; Zhang, Ren-Gang; Yun, Quan-Zheng; et al. (Frontiers in Plant Science, 2021)
Sour or wild jujube fruits and dried seeds are popular food all over the world. In this study, we reported a high-quality genome assembly of sour jujube (Ziziphus jujuba Mill. var. spinosa), with a size of 406 Mbp and scaffold N50 of 30.3 Mbp, which experienced only γ hexaploidization event, without recent genome duplication. Population structure analysis identified four jujube subgroups (two domesticated ones, i.e., D1 in West China and D2 in East/SouthEast China, semi-wild, and wild), which underwent an evolutionary history of a significant decline of effective population size during the Last Glacial Period. The respective selection signatures of three subgroups were discovered, such as strong peaks on chromosomes #3 in D1, #1 in D2, and #4 in wild. Genes under the most significant selection on chromosomes #4 in wild were confirmed to be involved in fruit variations among jujube accessions, in transcriptomic analysis. Our study offered novel insights into the jujube population structure and domestication and provided valuable genomic resources for jujube improvement in stress response and fruit flavor in the future.